2017
DOI: 10.3126/jnps.v36i3.16357
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intelligence of Duchenne Muscular Dystrophy (DMD) Children and Adolescents and Parental Stress in a Muscular Dystrophy Center in Nepal

Abstract: Introduction: Duchene Muscular Dystrophy (DMD) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…Cognitive stratification based on IQ showed a similar distribution to that in the literature: 28% (normal IQ), 19% (borderline intelligence), 25% (mild ID), and 6% (moderate ID). Severe ID and profound ID has been estimated in 0.4% to 10% and 0.08% of patients [2][3][4][5][6][7][8][9][10], but we did not find these categories in our sample. There was a clear decreasing gradient of mean MMSE total score in four cognitive categories: 24 ± 4.9 (normal IQ), 23.1 ± 4.5 (borderline IQ), 18.6 ± 6 (mild ID), and 12.5 (moderate ID) (r s = 0.52, P < 0.001).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Cognitive stratification based on IQ showed a similar distribution to that in the literature: 28% (normal IQ), 19% (borderline intelligence), 25% (mild ID), and 6% (moderate ID). Severe ID and profound ID has been estimated in 0.4% to 10% and 0.08% of patients [2][3][4][5][6][7][8][9][10], but we did not find these categories in our sample. There was a clear decreasing gradient of mean MMSE total score in four cognitive categories: 24 ± 4.9 (normal IQ), 23.1 ± 4.5 (borderline IQ), 18.6 ± 6 (mild ID), and 12.5 (moderate ID) (r s = 0.52, P < 0.001).…”
Section: Discussioncontrasting
confidence: 75%
“…63%) [2][3][4][5][6][7][8][9][10][11][12], borderline intelligence (10% to 26%) [6][7][8], mild ID (15% to 27%) [2,6,10,11], moderate ID (6.7% to 10%) [2,10], severe ID (0.4% to 10%) [2,10], and profound ID (0.08%) among DMD patients [2]. Several studies have found an overall reduction of intelligence quotient (IQ) in boys with DMD, by the Wechsler scale, recording total scores from 76 to 90.2 [2][3][4][5][6][7]9,[13][14][15].…”
mentioning
confidence: 99%
“…Of the 2913 records initially identified (Figure S1), 59 were read in full text, of which 49 met the inclusion/exclusion criteria and were included in the systematic review (Table S1) 31–79 (47 of them in the meta‐analyses 32–39,41–79 ), while 10 were excluded for not including the outcome of interest or for other justified reasons (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Children with DMD stop walking (Birnkrant et al, 2018) approximately between the ages of 10 and 12. In some children, their cognitive ability is also compromised (Anikiej, Mánski, & Bidzan, 2018;Naidoo & Anthony, 2020), while in others it is preserved intact (Rana et al, 2016).…”
Section: Introductionmentioning
confidence: 99%